DETERMINAN ANGKA PARTISIPASI SEKOLAH (APS) TINGKAT PROVINSI DI PULAU JAWA, BALI, DAN NUSA TENGGARA - Eka Yulia Ningsih (2022)
Differences in resources owned by the community in each province in Java, Bali, and Nusa Tenggara also cause differences in accessing educational facilities. This study aims to determine the effect of income per capita, poverty rate, education sector spending, and the number of educators on the School Participation Rate (APS) in all provinces in Java, Bali, and Nusa Tenggara. The sampling in this study used a saturated sampling technique in nine (9) provinces during 2015-2019, so that a total sample of 45 data was obtained from the Central Statistics Agency and the Ministry of Education and Culture. This study uses panel data analysis by combining time-series data and cross-section data. The fixed-effect model was selected in this study and partially shows that income per capita, poverty rate, education sector spending, and number of educators have a significant effect on APS. The results of the study simultaneously show that income per capita, poverty rate, education sector spending, and number of teaching staff have an effect on APS.